Civility and Civil Religion before and after the French Revolution: Religious and Secular Rituals in Hume and Tocqueville - Spyridon Tegos (Genealogy, 2020)
In his critique of religion, Hume envisages forms of religious ritual disconnected from the superstitious “neurotic” mindset; he considers simple rituals fostering moderation. In this paper, I claim that one can profitably interpret Hume’s obsession with secular rituals, such as French highly ceremonial manners, in the sense of anxiety-soothing institutions that bind citizenry without the appeal to a civil religion, properly speaking. Let us call this path the Old Regime’s civil ritualism”. Overall, Tocqueville conceives rituals in a Humean spirit, as existential anxiety-soothing institutions. Moving beyond the Humean line of thought, he focuses on the ambiguous role of religious rituals in the context of democratic faith and the Christian civil religion that he deems appropriate for the US. Yet, he also detects novel forms of superstition firmly embedded in secular, democratic faith.